Soft soil, black grapes : the birth of Italian winemaking in California - Cinotto, Simone (Nation of newcomers., 2016)
From Ernest and Julio Gallo to Francis Ford Coppola, Italians have shaped the history of California wine. In this account of the ethnic origins of California wine, Simone Cinotto rewrites a century-old triumphalist story.